Characteristics and antibacterial potency of actinomycetes isolated from nypa palm litter - RIKHSAN KURNIATUHADI; TRI RIMA SETYAWATI; ARI HEPI YANTI; ANNISA FADHILA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kurniatuhadi R, Setyawati TR, Yanti AH, Fadhila A. 2024. Characteristics and antibacterial potency of actinomycetes isolated from nypa palm litter. Biodiversitas 25: 3449-3459. Actinomycetes are ubiquitous bacteria which are known to produce secondary metabolites with bioprospecting potential as antibacterial agents. This research aimed to qualitatively determine the density and diversity of this group, as well as the antibacterial potential of actinomycetes from nypa palm (Nypa fruticans (Thunb.) Wurmb.) litter. Isolation was performed using the pretreatment pour plate method, which involved wet heat treatment using a selective starch casein agar (SCA) medium. Actinomycetes density was calculated using the standard plate count (SPC). The isolated microorganisms where characterized based on macroscopic, microscopic characters, and biochemical tests. Potential antibacterial activity against Aeromonas sp. NrBF9 was qualitatively assessed employing the cross-streak method. The results showed that actinomycetes accounted for 11% of the total bacterial density. Macroscopic screening of the isolates’ colony characteristics revealed the successful retrieval and culture of eight isolates. All isolates exhibited similar characteristics to those of the genus Pseudonocardia. Six out of the eight isolates, coded as TCN1, TCN2, TCN4, TCN5, TCN6, and TCN7, could inhibit the activity of Aeromonas sp. NrBF9, resulting in the formation of a clear zone surrounding of colonies. The six isolates of Pseudonocardia with antibacterial activity have the potential to be developed as feed additives for nypa palm worm aquaculture.